A preliminary study of the combination of ultrafast and abbreviated dynamic contrast: Enhanced breast magnetic resonance imaging. Issue 50 (11th December 2020) - Jeong, Seok-min; Ha, Su Min; Ahn, Hye Shin; Woo, SeungTae; Sung, Jae Kon; Shin, Hee-Chul
Abstract : Abstract: We combined the abbreviated and ultrafast magnetic resonance imaging (MRI) technique with the standard MRI protocol and compared lesion characterization quantitatively and qualitatively to the standard MRI protocol. Fifty-six patients with breast cancer who underwent MRI from June 2017 to May 2018 and fulfilled our inclusion criteria were included. Three radiologists measured the lesion sizes, described the MRI findings using BI-RADS lexicon, and demarcated the regions of interest to extract the volumetric quantitative and semi-quantitative parameters. We used Pearson's correlation analysis comparing the quantitative and semi-quantitative parameters. To evaluate the inter-observer variability, we calculated the intra-correlation coefficient (ICC). We also analysed the correlation in BI-RADS lexicon. There were 45 (80.4%) luminal and 11 (19.6%) non-luminal breast cancers, and the most common tumour subtype was invasive carcinoma (n = 48, 85.7%), followed by ductal carcinoma in situ (n = 8, 14.3%). Regarding correlation between the quantitative and semi-quantitative parameters, K trans significantly correlated with the wash-in factor (r, 0.862; P < .001) and AUC value (r, 0.951; P < .001). The lesion size measured by standard and combined abbreviated-ultrafast phases and that from the surgical pathological specimens showed moderate agreement (ICC range, 0.516−0.578). The ICCs among the 3 readers were excellent for lesion size measurement, BI-RADS lexicon regarding lesion type, mass shape, margin, internal enhancement, non-mass enhancement distribution, and internal enhancement by the standard and combined abbreviated-ultrafast protocols. The use of the modified and combined abbreviated-ultrafast MRI protocol provides a reliable measurement of the quantitative parameters and may aid in the screening of breast cancer.